The benefits of differential diagnostic algorithm application to the surgical practice through the example of pseudomembranous colitis - L. A. Averyanova; A. A. Baulin; O. A. Baulina; V. A. Baulin; D. D. Lipatova (Сибирский научный медицинский журнал)
Aim of the study was to demonstrate the clinical observation of a patient with pseudomembranous colitis occurring under a gastroenterological clinical simulation of acute pancreatitis. Patient S., 68 years old, was taken several times by emergency medical personnel or admitted independently to medical institutions with recurrent abdominal syndrome. Using the diagnostic algorithm presented in the work, the patient was diagnosed with leukocytosis up to 12×109/l, a decrease in the total protein content to 42 g/l, and an increase in the creatinine level to 90.2 μmol/l. Colonoscopy and bacteriological examination of feces revealed – pale grayish-yellow plaques ranging in size from 0.5 to 2.0 cm in diameter on a slightly raised base. Against the background of areas of hyperemia of the colon mucosa, multiple fibrinous overlays were detected in all parts of the colon. Microscopically, pseudomembranes consisted of necrotic epithelium with fibrin effusion and neutrophils. Timely diagnosis allowed the patient to be hospitalized in a specialized hospital and to prescribe adequate treatment according to Clinical recommendations, to exclude possible complications.Conclusions. The diagnostic algorithm presented in the work demonstrated the effectiveness of its application to practice and showed perspectiveness on this direction with further research on other nosologies manifested by abdominal pain syndrome.